PERAN HUMAS DALAM MENINGKATKAN CITRA SMA MUHAMMADIYAH 1 PALANGKA RAYA - Hidayat, Rahmat; Zamzam F, Koyimatul (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This study aims to determine the implementation of the role of public relations in SMA Muhammadiyah 1 P. Raya and the media used in improving the positive image of the school. The type of research used is descriptive qualitative, the research subject consists of 5 informants, namely, vice head of public relations, teachers, students, alumni and the surrounding community. Using data collection techniques by means of interviews, observation and documentation. Data analysis uses data reduction techniques, data presentation and conclusion drawing. To ensure the validity of the data using triangulation techniques sources and methods. The results showed that the public relations role of SMA Muhammadiyah 1 P.Raya could be said to be optimal even though it was by concurrent positions. The results show that the role of public relations has carried out its role as communicator, relationship builder, back up management and corporate image, the communication process in improving the image of both internal and external publics can be said to be balanced with the same goal. The use of media is direct and mass media such as Facebook and WhatsApp, billboards, and brochures